1982
DOI: 10.1021/jo00346a031
|View full text |Cite
|
Sign up to set email alerts
|

Efficient "one-pot" synthesis of N-tritylamino acids

Abstract: A sequential procedure has been developed whereby neutral amino acids 1 were tritylated via their corresponding trimethylsilyl esters 2 to afford, after mild hydrolysis, IV-trityl amino acids 3 in high yields and purity. Hydroxy amino acids 4 were preferentially tritylated at the amino function by using either Me3SiCl or Me^iCtj (or Ph^iCy for temporary protection of the hydroxy and carboxyl groups. Finally, !Vim-tritylhistidine (9c) was prepared in 97% yield with the aid of the Me2SiCl2, whereas the use of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
7

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 0 publications
1
79
0
7
Order By: Relevance
“…400,396 -N τ -Trityl (Trt): It is the usual protecting group for the Fmoc/ t Bu strategy. 20,401 It is removed with 95% TFA but is much less acid-labile than the N α -trityl group and cannot be selectively removed in the presence of t Bu groups. 402 Using N τ protection, the free N π can still catalyze racemization.…”
Section: N Nhmentioning
confidence: 99%
See 1 more Smart Citation
“…400,396 -N τ -Trityl (Trt): It is the usual protecting group for the Fmoc/ t Bu strategy. 20,401 It is removed with 95% TFA but is much less acid-labile than the N α -trityl group and cannot be selectively removed in the presence of t Bu groups. 402 Using N τ protection, the free N π can still catalyze racemization.…”
Section: N Nhmentioning
confidence: 99%
“…An example of the former is the use of trimethylsilyl esters of amino acids prepared in situ, 18,20 -Trityl (Trt). 28,29 It is removed with 1% TFA in DCM or 0.1M HOBt in 2,2,2-trifluoroethanol (TFE) in solution.…”
Section: Introductionmentioning
confidence: 99%
“…To a solution of N-Trt-L-methionine [15] (150 g, 383 mmol) in 100 ml ethyl acetate 100 ml (1.605 mol) of Mel were added and the mixture was refluxed with stirring for 4 h. The thus produced solid material was filtered off and washed well with ethyl acetate, Et^O and petroleum ether. The obtained light yellow powder was dried in vacuo (KOH and P205).…”
Section: N-trityl-s-methyl-methionine Sulfonium Iodide (7)mentioning
confidence: 99%
“…Moreover, the preparation of 3 in pure form was not always successful in our hands. Naturally, compound 4 can be converted smoothly to the corresponding diethylamine salt 6 in crystalline form and high yield.Already we have reported that 5 can be easily prepared in high yield [15], Treatment of 5 with excess Mel under reflux in ethyl acetate produced the quaternary salt 7 in 75% yield. Treatment of 7 with two equivalents of KOH in H20-THF followed by controlled acidification and addition of diethylamine gave finally the diethylammonium salt 6 in 74% yield [2]).…”
mentioning
confidence: 99%
See 1 more Smart Citation